Tetrahydroisoquinoline-7-carboxamide derivatives as new selective discoidin domain receptor 1 (DDR1) inhibitors - Bullock, A; Wang, Z; Zhang, Y; Bartual, S; Luo, J; Xu, T; Du, W; Xun, Q; Tu, Z; Brekken, R; Ren, X; Liang, G; et al. (American Chemical Society, 2017)
Acute lung injury (ALI) is a deadly symptom for serious lung inflammation. Discoidin Domain Receptor 1 (DDR1) is a new potential target for anti-inflammatory drug discovery. A new selective tetrahydroisoquinoline-7-carboxamide based DDR1 inhibitor 7ae was discovered to tightly bind the DDR1 protein and potently inhibit its kinase function with a Kd value of 2.2 nM and an IC50 value of 6.6 nM, respectively. The compound dose-dependently inhibited lipopoly-saccharide (LPS)-induced interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) release in mouse primary peritone-al macrophages (MPMs). In addition, 7ae also exhibited promising in vivo anti-inflammatory effects in a LPS-induced mouse ALI model. To the best of our knowledge, this is the first “proof of concept” investigation on the potential appli-cation of a small molecule DDR1 inhibitor to treat ALI.